2019
DOI: 10.3906/sag-1811-41
|View full text |Cite
|
Sign up to set email alerts
|

High neutrophil-to-lymphocyte ratio predicts acute allograft rejection in kidney transplantation: a retrospective study

Abstract: Background/aim: Our research focused on the identification of easily available and sensitive markers for early prediction of acute kidney allograft rejection (AR). We aimed to investigate the association between neutrophil-to-lymphocyte ratio (NLR) and AR in kidney transplant patients. Materials and methods: The medical records of 51 kidney transplant patients [12 female/39 male; median age of 32 (IQR: 24-44) years] were evaluated retrospectively. We considered a cutoff value of >2.5 as high NLR. Results: A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…In this regard, NLR is considered amongst the independent predictors of the risk of AR (18)(19)(20). Ergin et al (16) reported that NLR values >2.5 were associated with AR (median NLR 4.06 vs. 1.24) in kidney transplant patients. In a study investigating early allograft rejection and NLR rate in 1531 liver transplant patients, the NLR rate was found to be significantly higher in patients with rejection (median 3.49 vs. 2.07) and NLR ≥2,85 (OR=1.89) was an independent predictor of early allograft rejection (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, NLR is considered amongst the independent predictors of the risk of AR (18)(19)(20). Ergin et al (16) reported that NLR values >2.5 were associated with AR (median NLR 4.06 vs. 1.24) in kidney transplant patients. In a study investigating early allograft rejection and NLR rate in 1531 liver transplant patients, the NLR rate was found to be significantly higher in patients with rejection (median 3.49 vs. 2.07) and NLR ≥2,85 (OR=1.89) was an independent predictor of early allograft rejection (21).…”
Section: Discussionmentioning
confidence: 99%
“…NLR and PLR are inflammatory markers that are inexpensive and readily available in routine clinical practice. Growing evidence exists regarding the predictive value of these markers in several conditions such as cancer, cardiovascular disease, rheumatic diseases, infections and transplantations (7,(12)(13)(14)(15)(16)(17). Additionally there are studies showing that NLR and PLR levels are positively correlated with inflammatory cytokines in patients with end-stage renal disease (15).…”
Section: Discussionmentioning
confidence: 99%
“…Higher tacrolimus (TAC) trough concentration derived markers, TAC-intrapatient variability (TAC-IPV or TAC-CV) [ 13 , 14 ], and TAC-time in therapeutic range (TAC-TTR) [ 15 ], were extensively proven to be strongly linked with subsequent composite poor outcomes in transplant patients. Furthermore, estimated glomerular filtration rate (eGFR) related novel markers including eGFR-coefficient of variation (eGFR-CV) [ 16 , 17 ], as well as inflammatory markers calculated from complete blood count (CBC) data, such as neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and monocyte-to lymphocyte ratio (MLR) [ 18 20 ], were shown to be associated with adverse events in KTRs. Therefore, we hypothesized that adding these relatively new markers to prognostic models may provide additional information to improve the risk assessment of allograft loss in KTRs.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, research on the transplant community has given increasing attention to the development and identification of novel biomarkers that allow for rapid, safe, non-invasive, and accurate detection of immunological injury to the kidney allograft (4, 5). Of particular interest are prognostic and predictive biomarkers that can identify patients at increased risk for allograft injury, including DGF and AR (6, 7).The neutrophil-to-lymphocyte ratio (NLR) and platelet-tolymphocyte ratio (PLR) are two biomarkers that provide an indication of inflammatory status and have been shown to be strong predictors of negative prognosis in a variety of conditions including cancer (8, 9), cardiovascular disease (10, 11), ESRD (12), and, more recently, kidney and liver transplantation (13)(14)(15)(16)(17)(18). Despite a growing body of evidence examining the utility of NLR and PLR to predict immunologic injury, the literature remains divided regarding the association between these inflammatory markers and development of DGF and AR.…”
mentioning
confidence: 99%
“…Despite a growing body of evidence examining the utility of NLR and PLR to predict immunologic injury, the literature remains divided regarding the association between these inflammatory markers and development of DGF and AR. Specifically, while some studies have demonstrated an association between high NLR and PLR and development of DGF and AR (14,15,18), others report the opposite findings (16,17). This lack of consensus suggests a need for ongoing investigation to identify additional biomarkers capable of identifying patients at risk of post-transplant immunologic events.The systemic immune-inflammation index (SII) was recently introduced as a novel and powerful prognostic 3349 This article is freely accessible online.…”
mentioning
confidence: 99%